TINGKAT PENDIDIKAN DAN PEKERJAAN IBU BALITA DENGAN KEIKUTSERTAAN POSYANDU (D/S) - Endang Buda Setyowati (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: Achievement of Posyandu participation (D / S = Number of under-fives weighed divided by the total number of children under five in the village) in 2017 in West Ketapang in 2017 was 42.3%, national target 85%. From this data, the participation of Posyandu is below the target. And as a result, the child's growth and development are not monitored maximally. Thus, the study aims to determine the relationship of education and occupation of mothers of children under five with the participation of posyandu (D / S) in West Papua Pososandu in 2018. Method: The research method uses analytic design with cross sectional surveys, the population is all mothers of toddlers in West Papua Pososandu in 2018 as many as 521. people, probability sampling in systematic random sampling was obtained as many as 227 people, using secondary data: registers, KMS, processed with frequency tables, cross tabulation, analyzed by Chi-Square test. Results: The results obtained by the majority of low educated 59.47% (135 people), the majority did not work 64.76% (147 people), active posyandu (D / S) participation 61.23% (139 people), while cross tabulation obtained a high-educated majority active in Posyandu (D / S) participation (72.82%) than low education (46.67%), and Chi-Square test analysis obtained ?2Calculate> ?2Table ie 8.76> 3.84, then Ho refused. The majority of non-working mothers are active in posyandu (D / S) participation (70.74%), compared to working (56.25%), and the Chi-Square test analysis obtained itung2Calculate> ?2Table ie 15.89> 3, 84, then Ho is rejected. Discussion: there is a relationship between education and the work of mothers of children under five with the participation of D / S posyandu in posapandu ketapang barat in 2018. Therefore there needs to be an approach, counseling and motivation to mothers of toddlers about the importance of posyandu through home visits and village community deliberations